Cervical Ossification of the Posterior Longitudinal Ligament: A Computed Tomography–Based Epidemiological Study of 2917 Patients. Issue 8 (December 2019) - Bakhsh, Wajeeh; Saleh, Ahmed; Yokogawa, Noriaki; Gruber, Jillian; Rubery, Paul T.; Mesfin, Addisu
Study Design: Retrospective cohort study. Objectives: To identify prevalence of ossification of the posterior longitudinal ligament (OPLL) of the cervical spine in a large sample, to characterize spinal involvement, and to identify associations with patient characteristics. Methods: Computed tomography (CT) scans of all patients receiving cervical spine CT imaging in a level-1 emergency department from January 1, 2014 to December 31, 2014 were reviewed. Diagnosis and classification of OPLL was performed, and data for associated patients was obtained (age, sex, race, ethnicity, body mass index, diabetes). US Census data was referenced for the sample population. Statistical analysis included t test and chi-square testing, with significance cutoff P < .05. Results: There were no significant differences between the sample and population data. Of 2917 patients reviewed, 74 exhibited OPLL (2.5%). Age distribution between OPLL and non-OPLL cohorts was significantly different ( P < .01), with highest prevalence of OPLL between ages 40 to 49 and 50 to 59 years. Comorbid diabetes also differed between groups (27% OPLL, 13% non-OPLL, P < .01). There was no difference in distribution of sex, race, or ethnicity. For OPLL, segmental type is most common (67.6%), involving on average 3.4 levels. OPLL involvement begins at any level, but ends most commonly at C6 (40.5%) or C7 (36.5%). Among OPLL patients, 18 (24.3%) demonstrated concurrent ponticulus posticus. Conclusions: This review of 2917 patients reaffirms previous data, with OPLL prevalence of 2.5%. In asymptomatic patients, incidental diagnosis is frequently seen as early as ages 40 to 49 years. OPLL is better characterized with a significant association with diabetes, segmental type being the most common, and the caudal extent typically involving C6-7 (77%).